Assistance in the Use of PROLANIS Cader Guidebook For Health Cadres in The Work of Kujangsari Health Centre - Nandang Jamiat; Fikri Nurul Fadli (ABDIMAS: Jurnal Pengabdian Masyarakat, 2023)
WHO (2016) stated that the number of people with Type II Diabetes Mellitus (type 2) worldwide amounted to 422 million people, while the number of DM sufferers in Indonesia rose from 6.9% to 8.5%. In West Java, the data for DM sufferers is around 31 thousand people (2017), while the number of DM patients in Bandung is 22,996 people, and the number of deaths caused by DM is 507 people (2019). The Chronic Disease Management Program (prolanis) is a healthcare system and a proactive approach implemented in an integrated manner involving participants/ sufferers of DM. One of the prolanis implementations going well is the Kujang Sari Health Center in Bandung City. The number of prolanis participants was 68 people. The activeness of the participants to check themselves, the understanding still needs to be comprehensive, and monitoring activities at home have yet to be carried out. Assistance to cadres is expected to increase the role of cadres in educating DM patients in their area. The cadre manual can be an effective medium for cadres in providing dietary assistance and education for DM patients.